2006
DOI: 10.1016/j.yexcr.2006.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for proximal tubule epithelial cell detachment in response to ischemia: Role of oxidative stress

Abstract: Sublethal renal ischemia induces tubular epithelium damage and kidney dysfunction. Using NRK-52E rat proximal tubular epithelial cells, we have established an in vitro model, which includes oxygen and nutrients deprivation, to study the proximal epithelial cell response to ischemia. By means of this system, we demonstrate that confluent NRK-52E cells lose monolayer integrity and detach from collagen IV due to: (i) actin cytoskeleton reorganization; (ii) Rac1 and RhoA activity alterations; (iii) Adherens juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…Previous studies have shown that reactive oxygen species mediates FA complex disassembly accompanied by FAK dephosphorylation and weakens FA-mediated cell matrix adhesion of tubular epithelial cells. 4 We confirmed that H 2 O 2 profoundly impaired FA stability by initiating FA turnover in both FAK-expressing and FAK-deficient cells. Although NF-B-mediated expression of MCP-1 and IL-6 36 increased in response to H 2 O 2 exposure, this was independent of FAK expression.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Previous studies have shown that reactive oxygen species mediates FA complex disassembly accompanied by FAK dephosphorylation and weakens FA-mediated cell matrix adhesion of tubular epithelial cells. 4 We confirmed that H 2 O 2 profoundly impaired FA stability by initiating FA turnover in both FAK-expressing and FAK-deficient cells. Although NF-B-mediated expression of MCP-1 and IL-6 36 increased in response to H 2 O 2 exposure, this was independent of FAK expression.…”
Section: Discussionsupporting
confidence: 71%
“…Cells were subjected to H 2 O 2 to mimic the in vivo biochemical perturbation caused by the oxidative stress associated with reperfusion after renal ischemia. 4 Culture medium samples were collected to determine the release of IL-6 and MCP-1. Although H 2 O 2 caused a time-dependent increase in both IL-6 and MCP-1 levels, no difference between FAK-expressing and FAK-deficient cells was observed (see Supplemental Figure S3 at http://ajp.amjpathol.org).…”
Section: Expression Of Fak Does Not Regulate Renal Inflammation Durinmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Ischemia impairs the capacity of the tubular epithelium to maintain the integrity of its cytoskeleton and affects adherens and tight junction stability [3][4][5] and cell-matrix interactions. 6 Loss of cell adhesion is one of the earlier responses of the tubular epithelium observed during IR injury, 7 preceding tubular epithelial-cell (TEC) death and inflammatory cell influx.…”
mentioning
confidence: 99%
“…According to some researchers, this drug is capable of inhibiting Ecadherin endocytosis and thus of preventing the loss of intercellular contact, an effect not suggested by the present study (Araujo et al, 2002;Sáenz-Morales et al, 2006). However, several studies have used chlorpromazine to protect against ischemia and reperfusion injuries (Joeschke, 2003;Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 57%